Biblioteca escolar e sala de leitura: narrativas docentes sobre a formação de leitores infantis - Silva, Maria Alice Carneiro Moraes (2024)
Reading is important for the development of the individual from an early age and the school library, as well as the reading room, are opportune spaces for the formation of the reader. From this perspective, this research chose as the central question of the study: What perceptions and teaching practices developed in the spaces of the School Library and Reading Room contribute to the formation of child readers? The general objective is to analyze how teachers conceive the training of child readers in the environment of the School Library and Reading Room in the space of a Municipal Early Childhood Education Center (CMEI) in the municipality of Feira de Santana. As specific objectives, investigate the contribution of the School Library and the Reading Room in the process of student reading training and identify the reading mediation practices developed by teachers to train child readers. As a methodological path, the research was anchored in a qualitative approach, using the case study as an investigation method and for data generation, semi-structured interviews, field diaries and questionnaires were chosen; The research collaborators were teachers from groups 3 and 5 of the CMEI under study. To analyze the data, content analysis based on Bardin (2020) was used. Among the theoretical references that anchor this research, Campello (2012), Milanesi (2013), Lima (2017, 2023) stand out, which bring reflections on the library and its historical context; on the importance of reading and reader training, the contributions of Cândido (2011), Petit (2008, 2019), Fragoso (2002), Colomer (2007), Lajolo (2002); Zilberman (2003, 2017); on public policies for the library, Oriá (2017), IFLA/UNESCO Manifesto, among others. Thus, this study focuses on looking at the Library and Reading Room at CMEIs with a focus on the contributions of teaching narratives to the formation of readers in childhood, above all, with reading as a form of enjoyment. The research findings revealed that the CMEI collection needs to consider the specificities of age groups and broaden the perspective of the plurality of literary genres and literatures, such as black and indigenous literatures, among others; revealed that law 12,244/2010 was not implemented within the stipulated deadline; teaching readings require greater investment in literary reading. In this way, this research aims to contribute so that the discussions highlighted here can reverberate so that the Reading Room and School Library spaces are structured and organized in a way that democratizes reading, and the child is a being with rights, starting with CMEI spaces.